A Review on Z-Numbers - Bahrami, Saeed; Yaakob, Razali; Azman, Azreen; Atan, Rodziah (International Journal of Engineering and Technology, 2018)
Reliable information is very important to make accurate and right decision. The concept of Z-number can be used to describe the real-life information into computer-understandable that is relates to the issue of reliability information. This concept has a potential for many application such as Engineering, Management, Education, Mathematics, and also in many other fields. In this paper, applications and methodologies of the Z-numbers are reviewed systematically since 2011 until 2018 from several online databases such as ScienceDirect, Springer, Emerald, Wiley, and Taylor & Francis. The studied articles are grouped into four categories: the concepts papers, new approach papers, develop methods, and application papers.Â Â